The role of personality traits and engagement factors towards the use of paid stickers in personal communication messages - Sudaporn Sawmong (F1000Research, 2022)
The study recommends that the creators of stickers, emoticons, and emojis should consider user personality features, sticker engagement, sticker simplicity of use, and the personal delight of users in the creative and communication process. The study concludes that perceived enjoyment and perceived ease of use have a large and favorable impact on the use of paid stickers. The study's main limitation was that it focused on one area of social media. This must be taken into account when applying the findings.
Keywords: Digital Communication and Language; Linguistics, Language Diversity, and Identity; Digital Marketing and Social Media